Merger notification: the necessity for adequately defining control - Cilombo, Chanel (Department of Commercial Law, 2018)
Company law notions of control are not always harmonious with those of competition law, and thus the former may need to create its own jurisprudence informed by an appreciation of the purpose of merger notification under the Competition Act 89 of 1998. My research in this study will examine the definitions of control under the Competition Act (the "Act"),in terms of section 12(1) and section 12(2) comparatively to that of a company law notion of control as set out by the Companies Act, in terms of section 2, section 3, and section 123. In addition to sections 13A(3), 14A(1), 16(2) and 17, setting out merger notification and implementation, compulsory notification necessitated by large concentrations that require commission approval, as well as transactions that require tribunal approval after referral from the commission, and lastly the Competition Appeal Court merger proceedings in order to set aside a Tribunal decision to set conditions on a merger or to prohibit it. A further subtopic for examination in this study being, when parties to a merger have failed to notify the authorities, how should the administrative penalty be calculated, as well as considering the potential for criminal sanctions for failure to notify.